Sikkha: A Viewpoint of Buddhism สิน งามประโคน๑, - งามประโคน, สิน; ชำนิศาสตร์, บุญเชิด (Journal of Educational Review Faculty of Education in MCU, 2018)
Sikkha means learning, study, training and searching for knowledge in a particular field. Sikkha is a method or process of acquiring knowledge for career and making a perfect man. In the Buddhist viewpoint, Sikkha is a virtue that can develop human both physically and mentally from ordinary happiness to deliverance from suffering.